1997
DOI: 10.1159/000190202
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemic Nephropathy Induced by Adriamycin: Effect of Melatonin Administration

Abstract: The effect of melatonin (MEL) on the nephropathy and the oxidative stress induced by a single and high dose of Adriamycin (AD) has been studied in Wistar male rats. MEL (50 μg/kg/day) was injected intraperitoneally 3 and 7 days, respectively, before and after AD injection (20 mg/kg i.p.). Trunk blood was drawn and triglycerides, total cholesterol, phospholipids, high-density lipoprotein cholesterol, urea, creatinine, total protein, lipoperoxides, and reduced glutathione (GSH) levels and catalase activity (CAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
36
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 13 publications
13
36
0
Order By: Relevance
“…35 Another important inflammatory cytokine, IL-6, exhibits many physiological effects. 36 Contrast media administration was shown to lead to an increase in the levels of IL-6 in the kidney, 38 while TNF-a led to an increase in NF-kB. 51,52 In our study, NF-kB upregulation, in parallel with contrast media and glycerol administration, correlated with the increasing levels of TNF-a and IL-6.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…35 Another important inflammatory cytokine, IL-6, exhibits many physiological effects. 36 Contrast media administration was shown to lead to an increase in the levels of IL-6 in the kidney, 38 while TNF-a led to an increase in NF-kB. 51,52 In our study, NF-kB upregulation, in parallel with contrast media and glycerol administration, correlated with the increasing levels of TNF-a and IL-6.…”
Section: Discussionsupporting
confidence: 53%
“…The latest literature states that melatonin averts nephrotoxicity triggered by several drugs. [33][34][35][36][37][38] In particular, Gazi et al 39 demonstrated the defensive effect of melatonin administration in rat radiocontrast nephrotoxicity by reducing BUN and creatinine levels. 40 However, these studies have not measured oxidative and molecular parameters to indicate whether regeneration of the kidneys occurred after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Significant inhibition of MDA in both plasma and kidney tissue by melatonin may be due to its antioxidant effect. In serum and kidney tissue, melatonin significantly reverted the Adriamycin-induced increase in lipid peroxide [23]. Simultaneous administration of melatonin also significantly reduced lipid peroxidation induced by paraquat, bacterial lipopolysaccharide, and hydrogen peroxide [47].…”
Section: Discussionmentioning
confidence: 99%
“…In rats, melatonin, through its antioxidant properties, protected the animals from Adriamycin-induced nephropathy [23]and cardiomyopathy [24]. The antioxidant action of melatonin is also supported by results of experiments showing that it decreases the DNA damage caused by ionizing radiation in cultured cells [25]and by safrole in experimental animals [26]and that it also protects cells, tissues, and organs against oxidative damage caused by paraquat [27], lipopolysaccharide [28], glutathione depletion [29], and ischemic reperfusion [30].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative status is particularly relevant in renal tissue where a highly regulated antioxidant enzyme system has been demonstrated [23]. Furthermore, the administration of antioxidants (β-carotene, α-tocopherol and melatonin) and superoxide dismutase significantly decrease the biochemical parameters of the oxidative stress observed in AD-induced nephropathy, especially proteinuria [24, 25, 26]. …”
Section: Discussionmentioning
confidence: 99%